POSTOPERATIVE COGNITIVE DYSFUNCTION – WHAT WE KNOW AND WHERE WE GO - Yu. S. Polushin; A. Yu. Polushin; G. Yu. Yukina; M. V. Kozhemyakina (Вестник анестезиологии и реаниматологии, 2019)
The authors reviewed the literature and presented results of their own research of post-operative cognitive dysfunction confirming its social importance. The development of post-operative cognitive dysfunction is to be perceived as a real fact despite the differences in the published epidemiological data. Currently, there are no grounds to correlate it directly with the general anesthesia given to patients, and there is no evidence that a certain method of anesthesia or a certain drug can reduce the frequency of post-operative clinical decline. There are numerous factors within genesis of post-operative cognitive decline and they are not studied well. All suspected mechanisms (neurotoxicity of the used agents, and other factors of anesthesia and surgery; impairment of information neuro-transmission mechanisms; neuroinflammation developing as a response to trauma) can initiate the complex neuro-physiological reactions causing cognitive dysfunction.The authors presented experimental data about morphofunctional changes in neurons and cerebellar cortex microglia after laparotomy and anesthesia with sevoflurane followed by the exposure to it in a special box for 6 hours (induction of 8 vol. % with the air flow of 2 l/min., maintaining 2 vol. % of sevoflurane with the air flow of 1 l/min.). They demonstrated that neuroinflammation was not the key factor of the detected neuronal damage. Purkinje neurons were damaged the most, since they were fairy sensitive to energy metabolic disorders, promoting the death of other neurons of the molecular layer. Neurons of the granular layer with the low level of energy metabolism were the most resistant to the impact provided by surgery/anesthesia. These data confirmed the importance of multifactorial approach when assessing the genesis of cognitive dysfunction. This research is to be continued and aimed to find out predictors of post-operative cognitive decline and to optimize anaesthesiologic support of surgery and other invasive interventions to provide a balance between their aggressiveness and effectiveness of protection, especially in senile patients who already have some cognitive dysfunctions.